Severe asymptomatic hypophosphataemia in a child with T-acute lymphoblastic leukaemia - Zakaria, N.H.; Sthaneshwar, P.; Shanmugam, H. (Malaysian Society of Pathologists, 2017)
Hypophosphataemia is a metabolic disorder that is commonly encountered in critically ill patients. Phosphate has many roles in physiological functions, thus the depletion of serum phosphate could lead to impairment in multiple organ systems, which include the respiratory, cardiovascular, neurological and muscular systems and haematological and metabolic functions. Hypophosphataemia is defined as plasma phosphate level below 0.80 mmol per litre (mmol/L) and can be further divided into subgroups of mild (plasma phosphate of 0.66 to 0.79 mmol/L), moderate (plasma phosphate of 0.32 to 0.65 mmol/L) and severe (plasma phosphate of less than 0.32 mmol/L). The causes of hypophosphataemia include inadequate phosphate intake, decreased intestinal absorption, gastrointestinal or renal phosphate loss, and redistribution of phosphate into cells. Symptomatic hypophosphataemia associated with haematological malignancies has been reported infrequently. We report here a case of asymptomatic severe hypophosphataemia in a child with acute T-cell lymphoblastic leukaemia. A 14-year-old Chinese boy was diagnosed to have acute T cell lymphoblastic leukaemia (ALL). His serum biochemistry results were normal except inorganic phosphate and lactate dehydrogenase levels. The serum inorganic phosphate level was 0.1mmol/L and the level was low on repeated analysis. The child had no symptoms related to low phosphate levels. The possible causes of low phosphate were ruled out and urine Tmp/GFR was normal. Chemotherapy regime was started and the serum phosphate levels started to increase. Hypophosphataemia in leukaemia was attributed to shift of phosphorus into leukemic cells and excessive cellular phosphate consumption by rapidly proliferating cells. Several reports of symptomatic hypophosphataemia in myelogenous and lymphoblastic leukaemia in adults have been reported. To our knowledge this is the first case of severe asymptomatic hypophosphataemia in a child with ALL.